2017
DOI: 10.1080/15358593.2017.1331254
|View full text |Cite
|
Sign up to set email alerts
|

More to the story: how the medical humanities can learn from and enrich health communication studies

Abstract: The fields of communication studies and the medical humanities intersect and inform each other in interesting and important ways; and yet, these connections are rarely made explicit. As such, this special collection of articles from scholars in diverse fields such as disability studies, communication studies, the medical humanities, philosophy, and medicine discuss the ways that these fields diverge and converge and what we can learn from one another when we dissolve disciplinary divisions. In this Guest Edito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Point (3) in figure 5 represents the calculated CRLB for a potential performance improvement with an optimized × 3 3 mm 2 active area version of the NUV-HD SiPMs. The SPTR of the × 3 3 mm 2 NUV SiPMs has been reported as 171 ps FWHM (Nemallapudi et al 2015), and an optimized × 40 40 μm 2 micro-cell layout has the potential to improve the effective PDE by about 15%, compared to the devices in this work, due to a better fill factor (Piemonte 2015). This CTR improvement, of course, only holds true if the same voltage above breakdown as shown in figure 4(a) can be achieved while maintaining a similar level of dark counts, after pulsing, and cross talk.…”
Section: Crystal Geometrymentioning
confidence: 85%
See 1 more Smart Citation
“…Point (3) in figure 5 represents the calculated CRLB for a potential performance improvement with an optimized × 3 3 mm 2 active area version of the NUV-HD SiPMs. The SPTR of the × 3 3 mm 2 NUV SiPMs has been reported as 171 ps FWHM (Nemallapudi et al 2015), and an optimized × 40 40 μm 2 micro-cell layout has the potential to improve the effective PDE by about 15%, compared to the devices in this work, due to a better fill factor (Piemonte 2015). This CTR improvement, of course, only holds true if the same voltage above breakdown as shown in figure 4(a) can be achieved while maintaining a similar level of dark counts, after pulsing, and cross talk.…”
Section: Crystal Geometrymentioning
confidence: 85%
“…These sensors improve on the fill factor of the previous generation of FBK NUV sensors (Pro et al 2013) to provide a higher effective photon detection efficiency (PDE). The NUV-HD SiPMs studied here have a × 4 4 mm 2 active area comprising 25 600 × 25 25 μm 2 individual cells, a dark count rate of 200 kHz at 9 V over breakdown, and an effective PDE of 53% for 400 nm photons at the same voltage (Piemonte 2015). The single photon timing resolution (SPTR) of × 3 3 mm 2 standard NUV sensors has been reported as 171 ps FWHM (Nemallapudi et al 2015).…”
Section: Silicon Photomultipliersmentioning
confidence: 99%
“…The assertation that humanities impact communication skills has been evidenced by a recent observational study from the USA: those who majored in the humanities and social sciences as their pre-med performed significantly better in their communication and interpersonal skills examination that those with natural science majors ( Hirshfield, Yudkowsky and Park, 2019 ). The theory of communication skills training, postulates that communication as a skill is transactional ( Piemonte, 2017 ) and our undergraduate curricula work along this basis. A literature review in 2018 ( Sanson-Fisher et al, 2018 ) looked at the methodological quality of research in communication skills, upon its review of 243 publications the authors reported that the majority of these were descriptive and not evidence based.…”
Section: Current Place Of Humanities Within the Medical Curriculummentioning
confidence: 99%
“…For both of these topics detailed analysis is not given, because no midwifery schools (and only the ways our future caregivers are educated." 16 anthropology, sociology and pedagogy are all much more likely to be present in the midwifery curriculum than the medical one. all of these topics enable students to understand how society shapes the views, experiences and expectations of health care users, and how they learn (about health and wellbeing and positive lifestyles, for instance).…”
Section: Philosophy (Literature and Arts) And Inter-multiculturalmentioning
confidence: 99%